Parent-Offspring Conflict over Mating: The Case of Mating Age - Menelaos Apostolou (Evolutionary Psychology, 2010)
Parents and offspring have asymmetrical preferences with respect to mate choice. So far, several areas of disagreement have been identified, including beauty, family background, and sexual strategies. This article proposes that mating age constitutes another area of conflict, as parents desire their children to initiate mating at a different age than the offspring desire it for themselves. More specifically, the hypothesis is tested that individuals prefer for their offspring to start having sexual relationships at a later age than they prefer for themselves to do so. Furthermore, it is hypothesized that individuals prefer to marry at a later age than they prefer their offspring to marry. Finally, the hypothesis is tested that parents prefer their daughters to marry at an earlier age and start sexual relationships later than their sons. Evidence from two independent studies employing 751 British parents provides support for all three hypotheses.